Active material particles, electrode, power storage element, and power storage device

By using the lithium transition metal compound with a polycinoma ion structure, the particles that are covered with carbon materials are used as active substance particles, which solve the problem of insufficient density of active material layers in the existing technology, and achieve a significant improvement of the volume discharge capacity of the unit.

CN119384736APending Publication Date: 2025-01-28GS YUASA INT LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380047731.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-06-05
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When a lithium transition metal compound having a polyanionic structure is used as an active substance in the prior art, it is difficult to increase the density of the active substance layer, resulting in insufficient discharge capacity per unit volume.

Method used

The particles containing lithium transition metal compounds containing a polyphonic ion structure are covered by carbon materials as active substance particles. The amount of particle size changes when these particles are pressed to 100mn by 20mn to be less than 1.1Nm, forming a high -density active substance layer.

Benefits of technology

By increasing the density of the active material layer, the discharge capacity of the unit volume has been significantly increased, and the problem of insufficient density of the active material layer in the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384736A_ABST
    Figure CN119384736A_ABST
Patent Text Reader

Abstract

Active material particles according to one aspect of the present invention are particles in which particles containing a lithium transition metal compound having a polyanion structure are coated with a carbon material, and the amount of change in particle diameter when pressurized from 20 mN to 100 mN is 1.1 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to active material particles, electrodes, electricity storage elements, and electricity storage devices. Background Art

[0002] Non-aqueous electrolyte secondary batteries, represented by lithium-ion non-aqueous electrolyte secondary batteries, are widely used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries are generally composed of an electrode body having a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are charged and discharged by the exchange of charge-transporting ions between the two electrodes. In addition, as storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and electric double-layer capacitors have also become widely popular.

[0003] Lithium transition metal compounds with polyanion structures, such as lithium iron phosphate, are known as positive electrode active materials used in energy storage devices. Patent Document 1 describes a non-aqueous electrolyte secondary battery comprising a positive electrode containing lithium iron phosphate as the positive electrode active material and a negative electrode containing graphite as the negative electrode active material. From the perspective of electronic conductivity, lithium transition metal compounds with polyanion structures are typically used in the form of particles coated with a carbon material.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2007-213961 Summary of the Invention

[0007] When a lithium transition metal compound having a polyanion structure is used as an active material, it is difficult to increase the density of the active material layer. Therefore, the discharge capacity per unit volume of electrodes and storage devices using lithium transition metal compounds having a polyanion structure is not sufficiently large.

[0008] The present invention has been made based on the above circumstances, and an object of the present invention is to provide active material particles capable of increasing the discharge capacity per unit volume of an active material layer, and an electrode, a storage element, and a storage device using such active material particles.

[0009] Active material particles according to one aspect of the present invention are granules comprising particles of a lithium transition metal compound having a polyanion structure coated with a carbon material, and the change in particle size when a pressure of 20 mN to 100 mN is 1.1 nm or less.

[0010] An electrode according to another aspect of the present invention includes the active material particles.

[0011] Another aspect of the present invention comprises an active material layer containing the active material particles, wherein the density of the active material layer is 1.8 g / cm 3 above.

[0012] A power storage device according to another aspect of the present invention includes this electrode.

[0013] A power storage device according to another aspect of the present invention includes two or more power storage elements and one or more of the power storage elements.

[0014] According to one aspect of the present invention, it is possible to provide active material particles capable of increasing the discharge capacity per unit volume of an active material layer, and an electrode, a power storage element, and a power storage device using such active material particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a perspective view showing one embodiment of an electric storage element.

[0016] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by a collection of a plurality of electricity storage elements. DETAILED DESCRIPTION

[0017] First, the active material particles, electrodes, and energy storage devices disclosed in this specification will be briefly described.

[0018] [1] The active material particles of one aspect of the present invention are granules comprising particles of a lithium transition metal compound having a polyanion structure coated with a carbon material, wherein the change in particle size when a pressure is applied from 20 mN to 100 mN is 1.1 nm or less.

[0019] The active material particles described in [1] above can increase the discharge capacity per unit volume of the active material layer. The reason for this has not yet been determined, but it is speculated to be the following. Conventional particles containing lithium transition metal compounds having a polyanion structure are relatively brittle. Therefore, when conventional particles containing lithium transition metal compounds having a polyanion structure are used, the particles deform and break during the pressing of the active material layer in the electrode manufacturing process, thereby reducing the volume density of the particles and, as a result, not sufficiently increasing the density of the active material layer. In contrast, the active material particles described in [1] above have a small amount of deformation during pressing, so they can form a high-density active material layer by pressing, thereby increasing the discharge capacity per unit volume of the active material layer.

[0020] The measurement of the change in the particle size of the active material particles is carried out when the battery is assembled as a positive electrode active material in a storage element and is in a fully discharged state by the following method. First, the storage element is charged with a constant current at a charging current of 0.05C until the charge termination voltage during normal use is reached, and the battery is fully charged. After 30 minutes of rest, constant current discharge is performed at a discharge current of 0.05C to the discharge termination voltage (lower limit voltage) during normal use. Disassemble and remove the positive electrode, and assemble a test battery using a metal lithium electrode as a counter electrode. Constant current discharge is performed at a current value of 10mA per 1g of positive electrode mixture until the positive electrode potential reaches 2.0V vs.Li / Li + , adjust the positive electrode to a fully discharged state. Disassemble and remove the positive electrode again. Use dimethyl carbonate to thoroughly clean the electrolyte and other substances attached to the removed positive electrode, and after drying at room temperature overnight, recover the active material particles. The recovered active material particles are provided for measurement. The operations from disassembling the storage element to recovering the active material particles are carried out in an argon atmosphere with a dew point below -60°C. "Under normal use" refers to the case where the storage element is used under the charging and discharging conditions recommended or specified for the storage element. For charging conditions, for example, when a charger for the storage element is configured, it refers to the case where the storage element is used with the charger.

[0021] The change in the particle size of the active material particles is measured by a micro compression test using a micro compression tester ("MCT-511" manufactured by Shimadzu Corporation). A diamond flat indenter with a diameter of 50 μm is used as the probe. One active material particle is pressurized at a probe speed of 0.134 mN / second, and the displacement of the probe within a pressure range of 20 mN to 100 mN is set as the change in particle size when the pressure is applied from 20 mN to 100 mN. In addition, the change in particle size is measured for 5 active material particles and the average value is used. The active material particles to be measured are selected from particles with a particle size of 1 / 2 to 2 times the average particle size of the active material particles. The "particle size" of each particle is set as the average value of the short diameter and the long diameter. The short diameter is set as the shortest diameter passing through the center of the minimum circumscribed circle of the particle, and the long diameter is set as the diameter passing through the above center and perpendicular to the short diameter. When there are two or more shortest diameters, the longest diameter perpendicular to the diameter is taken as the short diameter. The “average particle size” refers to a particle size distribution measured by a laser diffraction / scattering method using a dilution solution prepared by diluting particles with a solvent in accordance with JIS-Z-8825 (2013), and a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) becomes 50%.

[0022] [2] In the active material particles described in [1] above, the rate of change in particle size when the pressure is applied from 20 mN to 100 mN may be 0.05% or less. The active material particles described in [2] above can form an active material layer with a higher density, thereby further increasing the discharge capacity per unit volume of the active material layer. The rate of change in particle size is defined as the percentage of the change in particle size when the pressure is applied from 20 mN to 100 mN relative to the average particle size of the active material particles.

[0023] [3] Among the active material particles described in [1] or [2] above, the particles comprising a lithium transition metal compound having a polyanion structure may be secondary particles. Generally, when the particles comprising a lithium transition metal compound having a polyanion structure are secondary particles, deformation and rupture during pressing are particularly prone to occur, and thus the problem of the discharge capacity per unit volume of the active material layer not increasing becomes significant. Therefore, the active material particles described in [3] above significantly suppress deformation and rupture during pressing, thereby increasing the discharge capacity per unit volume of the active material layer, by making the particles comprising a lithium transition metal compound having a polyanion structure secondary particles. Secondary particles refer to particles formed by the aggregation of multiple primary particles.

[0024] [4] Another aspect of the present invention is an electrode comprising the active material particles described in any one of [1] to [3]. The electrode described in [4] comprises the active material particles described in any one of [1] to [3], so that the discharge capacity per unit volume of the active material layer is large.

[0025] [5] Another aspect of the present invention comprises an electrode comprising an active material layer containing the active material particles described in any one of [1] to [3] above, wherein the density of the active material layer is 1.8 g / cm 3 The electrode described in [5] above includes the active material particles described in any one of [1] to [3] above, and the density of the active material layer is high, so the discharge capacity per unit volume is large.

[0026] Active material layer density (g / cm 3 ) is a value calculated from the mass per unit area of ​​the active material layer and the average thickness of one active material layer. In other words, the "density" of the active material layer refers to the apparent density. The average thickness of the active material layer is the average of the thicknesses measured at any five locations.

[0027] [6] Another aspect of the present invention provides an electric storage device comprising the electrode described in [4] or [5]. The electric storage device described in [6] comprises the electrode described in [4] or [5] comprising the active material particles described in any one of [1] to [3], and thus has a large discharge capacity per unit volume of the active material layer.

[0028] [7] Another aspect of the present invention provides an electrical storage device comprising two or more electrical storage elements and one or more electrical storage elements as described in [6]. The electrical storage device as described in [7] comprises one or more electrical storage elements as described in [6], so the discharge capacity per unit volume of the active material layer is large.

[0029] The active material particles, the method for producing the active material particles, the electrode, the storage element, the storage device, the method for producing the storage element, and other embodiments of the present invention are described in detail. It should be noted that the names of the components (constituent elements) used in each embodiment may differ from the names of the components (constituent elements) used in the background art.

[0030] Active material particles

[0031] The active material particles according to one embodiment of the present invention are granular particles in which particles of a lithium transition metal compound having a polyanion structure are coated with a carbon material.

[0032] Examples of lithium transition metal compounds having a polyanion structure include compounds containing oxoacid anions (PO4 3- 、SO4 2- 、SiO4 4- , BO3 3- VO4 3- etc.), lithium ions and transition metal ions. Oxygen acid anions can be condensed anions (P2O7 4- 、P3O 10 5- The lithium transition metal compound having a polyanion structure may have an olivine-type crystal structure. The lithium transition metal compound having a polyanion structure is typically a polyanion compound containing lithium and a transition metal element, and may further contain other elements (such as halogen elements, etc.). As the transition metal element possessed by the lithium transition metal compound having a polyanion structure, iron, manganese, nickel and cobalt are preferred, and iron is more preferred. As the oxygen-containing acid anion possessed by the lithium transition metal compound having a polyanion structure, phosphate anion (PO4 3- ).

[0033] The lithium transition metal compound having a polyanion structure is preferably a compound represented by the following formula (1).

[0034] Li a M b (AO c ) d X e ···(1)

[0035] In formula (1), M is at least one transition metal element. A is at least one selected from B, Al, Si, P, S, Cl, Ti, V, Cr, Mo, and W. X is at least one halogen element. a, b, c, d, and e are numbers satisfying 0 < a ≤ 3, 0 < b ≤ 2, 2 ≤ c ≤ 4, 1 ≤ d ≤ 3, and 0 ≤ e ≤ 1. a, b, c, d, and e can be integers or decimals.

[0036] As M in formula (1), any one of Fe, Mn, Ni, and Co, or a combination of any two thereof is preferred. As M, Fe, Mn, or a combination thereof is further preferred, and Fe is more preferred. In addition, the Fe content in M ​​is preferably 50 mol% or more, more preferably 70 mol% or more, 90 mol% or more, or 99 mol% or more. As A, P is preferred. As X, F is preferred. In one embodiment, a=1, b=1, c=4, d=1, and e=0 are also preferred.

[0037] Specific examples of lithium transition metal compounds having a polyanion structure include LiFePO4, LiCoPO4, LiFe 0.5 Co 0.5 PO4, LiMnPO4, LiNiPO4, LiMn 0.5 Fe 0.5 PO4, LiCrPO4, LiFeVO4, Li2FeSiO4, Li2Fe2(SO4)3, LiFeBO3, LiFePO 3.9 F 0.2 , Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. The atoms or polyanions in these lithium transition metal compounds having polyanionic structures may be partially replaced by other atoms or anionic species. The lithium transition metal compounds having polyanionic structures may be used alone or in combination of two or more.

[0038] The content of the lithium transition metal compound having a polyanion structure in the particles containing the lithium transition metal compound having a polyanion structure may be 60% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more.

[0039] The particles comprising a lithium transition metal compound having a polyanion structure may be particles in which a plurality of primary particles exist independently without aggregation (single particles), but are preferably secondary particles formed by aggregation of a plurality of primary particles. Such particles are, for example, secondary particles of a lithium transition metal compound having a polyanion structure.

[0040] Particles containing a lithium transition metal compound having a polyanionic structure are coated with a carbon material to form active material particles according to one embodiment of the present invention. A portion of the carbon material may be present within the particles containing the lithium transition metal compound having a polyanionic structure. The active material particles may also have portions not coated with the carbon material (e.g., portions where the lithium transition metal compound having a polyanionic structure is exposed).

[0041] By coating particles of a lithium transition metal compound having a polyanion structure with a carbon material, the active material particles can exhibit sufficient electron conductivity between the particles. The carbon material is, for example, a material having a carbon content of 80% to 100% by mass. The carbon content in the carbon material can be 90% by mass or more, or 95% by mass. Elements other than carbon that can be contained in the carbon material include oxygen, hydrogen, nitrogen, etc. Examples of the carbon material include graphite, non-graphite carbon, etc.

[0042] The content of the carbon material in the active material particles is preferably 0.1% to 20% by mass, more preferably 0.2% to 10% by mass, further preferably 0.3% to 5% by mass, and even more preferably 0.5% to 2% by mass. By having the carbon material content in the active material particles be greater than or equal to the above lower limit, electronic conductivity, etc., can be improved. By having the carbon material content in the active material particles be less than or equal to the above upper limit, the content of the lithium transition metal compound having a polyanion structure can be increased, and the discharge capacity per unit volume of the active material layer can be further increased.

[0043] The total content of the lithium transition metal compound having a polyanion structure and the carbon material in the active material particles is preferably 90% to 100% by mass, and may be 95% by mass or more, 98% by mass or more, 99% by mass or more, or 99.9% by mass or more.

[0044] The upper limit of the change in particle size when the active material particles are pressurized from 20mN to 100mN is 1.1nm, preferably 1.0nm, and sometimes more preferably 0.9nm, 0.8nm, 0.7nm, 0.6nm, 0.5nm, 0.4nm or 0.3nm. By making the change in particle size below the above upper limit, the density of the active material layer can be increased, and the discharge capacity per unit volume of the active material layer can be increased. The lower limit of the change in particle size can be, for example, 0.001nm, 0.01nm, or 0.1nm. The change in particle size can be any of the above lower limits to any of the above upper limits.

[0045] The upper limit of the rate of change in particle size when the active material particles are pressurized from 20 mN to 100 mN is preferably 0.05%, more preferably 0.03%, even more preferably 0.015%, and sometimes even more preferably 0.012%, 0.010%, 0.008%, 0.006%, or 0.004%. By keeping the rate of change in particle size below the upper limit, the density of the active material layer can be further increased, and the discharge capacity per unit volume of the active material layer can be further increased. The lower limit of the rate of change in particle size can be, for example, 0.0001%, 0.001%, or 0.002%. The rate of change in particle size can be from any of the lower limits to any of the upper limits.

[0046] The average particle size of the active material particles is preferably 0.5 μm to 30 μm, more preferably 1 μm to 20 μm, further preferably 2 μm to 15 μm, further preferably 4 μm to 10 μm, and further preferably 6 μm to 8 μm. By having the average particle size of the active material particles be within the above range, the density of the active material layer can be further increased, and the discharge capacity per unit volume of the active material layer can be further increased. In order to obtain the active material particles with a specified average particle size, a pulverizer, a classifier, etc. can be used. As a pulverization method, for example, methods using a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotary airflow jet mill, or a sieve can be cited. Wet pulverization in which an organic solvent such as water or hexane coexists can also be used during pulverization. As a classification method, dry or wet sieves, wind classifiers, etc. can be used as needed.

[0047] <Method for producing active material particles>

[0048] The active material particles of one embodiment of the present invention can be efficiently obtained by adjusting the pH of the reaction solution using ammonia water or the like when manufacturing the hydroxide precursor in a method using a hydroxide precursor, a lithium source, and a carbon source. By such a manufacturing method, spherical active material particles can be obtained that are not easily deformed even when the particle shape is pressed. The manufacturing method is described in detail below. However, the active material particles of the present invention are not limited to being manufactured by the following manufacturing method.

[0049] First, a hydroxide precursor is obtained by a precipitation reaction of transition metal ions and hydroxide ions in water. Specifically, for example, a hydroxide precursor (transition metal hydroxide) is obtained by dropping a transition metal salt aqueous solution and a sodium hydroxide aqueous solution into water. As a transition metal salt, any salt containing a transition metal element constituting the target lithium transition metal compound and having water solubility can be used, for example, iron sulfate, iron chloride, cobalt sulfate, manganese sulfate, nickel sulfate, etc. can be used. In addition, potassium hydroxide aqueous solution, etc. can also be used instead of sodium hydroxide aqueous solution. When the transition metal salt aqueous solution and the sodium hydroxide aqueous solution are added dropwise to water, in order to keep the pH of the water (reaction solution) to which these aqueous solutions are added dropwise within a specified range, an ammonia aqueous solution, etc. is further added dropwise to the reaction solution. The pH of the reaction solution is preferably in the range of 8.5 to 10.5. In the case where the pH of the reaction solution deviates from the above range and even if the pH of the reaction solution is within the above range but the ammonia aqueous solution is not added dropwise to the reaction solution, the active material particles finally obtained tend to have a large change in particle size when pressurized. The concentration of the ammonia aqueous solution added dropwise can be, for example, 0.3 mol / dm 3 ~1mol / dm 3 The pH of the reaction solution can be adjusted by adjusting the concentration and amount of the ammonia solution, sodium hydroxide solution, etc. added dropwise. Other alkaline aqueous solutions such as hydrazine aqueous solution can also be added dropwise together with the ammonia solution. The pH of the reaction solution can also be adjusted by adjusting the amount of other alkaline aqueous solutions added dropwise.

[0050] Next, the obtained hydroxide precursor, lithium source and carbon source are mixed and calcined under an inert atmosphere (for example, a nitrogen atmosphere) to obtain active material particles according to one embodiment of the present invention. As a lithium source, compounds having a polyanion structure and containing lithium elements such as LiH2PO4, Li3PO4, and LiHSO4 can be used. In addition, as a lithium source, LiOH, lithium halide, etc. can be used. When the lithium source used is not a compound having a polyanion structure, a compound having a polyanion structure is further mixed and calcined. As a compound having a polyanion structure, salts of ammonium cations and polyanions such as NH4H2PO4, (NH4)3PO4, (NH4)2HPO4, (NH4)2SO4, and NH4VO3 can be used. As a carbon source, organic substances such as sucrose, lactose, maltose, sucrose, polyvinyl alcohol, and ascorbic acid can be used. As the calcination temperature, for example, it can be 500°C to 800°C.

[0051] Electrodes

[0052] An electrode according to one embodiment of the present invention includes active material particles according to one embodiment of the present invention. This electrode is an electrode for a power storage device. A positive electrode, which is an electrode according to one embodiment of the present invention, will be described below.

[0053] The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or through an intermediate layer.

[0054] The positive electrode substrate has electrical conductivity. Whether it has electrical conductivity is determined by measuring the volume resistivity of 10 -2 Ω·cm is used as the threshold value for judgment. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among them, from the viewpoints of potential resistance, high conductivity and cost, aluminum or aluminum alloys are preferred. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.

[0055] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within this range, the strength of the positive electrode substrate can be increased, and the energy density per unit volume of the storage device can be improved.

[0056] The intermediate layer is placed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent, such as carbon particles, to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The composition of the intermediate layer is not particularly limited; for example, it may contain a binder and a conductive agent.

[0057] The positive electrode active material layer contains the above-mentioned active material particles and optionally contains other components other than the above-mentioned active material particles, such as other positive electrode active materials, a conductive agent, a binder, a thickener, and a filler.

[0058] The active material particles contained in the positive electrode active material layer are the active material particles described above as one embodiment of the present invention. The content of the active material particles in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and even more preferably 80% to 95% by mass. By setting the content of the active material particles within the above range, it is possible to achieve both an increase in the discharge capacity per unit volume of the positive electrode active material layer and manufacturability.

[0059] The positive electrode active material layer may further include other positive electrode active materials other than the active material particles of one embodiment of the present invention. As other positive electrode active materials, various positive electrode active materials known in the past can be used. Wherein, relative to all the positive electrode active materials contained in the positive electrode active material layer (the total of the active material particles of one embodiment of the present invention and other positive electrode active materials), the content of the active material particles of one embodiment of the present invention is preferably 90% by mass or more, more preferably 99% by mass or more, and further preferably 100% by mass. By making the positive electrode active material substantially consist only of the active material particles of one embodiment of the present invention, the discharge capacity per unit volume of the positive electrode active material layer can be further increased.

[0060] The conductive agent is not particularly limited as long as it is a material with conductivity. Examples of such conductive agents include carbon materials, metals, and conductive ceramics. Examples of carbon materials include graphite, non-graphite carbon, and graphene-based carbon. Examples of non-graphite carbon include carbon nanofibers, pitch-based carbon fibers, and carbon black. Examples of carbon black include furnace black, acetylene black, and Ketjen black. Examples of graphene-based carbon include graphene, carbon nanotubes (CNTs), and fullerenes. Examples of the shape of the conductive agent include powdered and fibrous forms. As the conductive agent, one of these materials may be used alone, or two or more may be mixed and used. In addition, these materials may be composited and used. For example, a composite of carbon black and CNTs may be used. Among these, from the viewpoints of electronic conductivity and coating properties, carbon black is preferred, and acetylene black is preferred.

[0061] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, and more preferably 3% to 9% by mass. By setting the content of the conductive agent within this range, the energy density of the storage device can be improved. It should be noted that the content of the conductive agent does not include the carbon material contained in the active material particles of one embodiment of the present invention (the carbon material coating the particles containing the lithium transition metal compound having a polyanion structure).

[0062] Examples of adhesives include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, and polyimide; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber; and polysaccharide polymers.

[0063] The content of the binder in the positive electrode active material layer is preferably 1% to 10% by mass, more preferably 3% to 9% by mass. When the content of the binder is within the above range, the positive electrode active material can be stably retained.

[0064] As thickeners, for example, polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose can be mentioned. In the case where the thickener has a functional group that reacts with lithium or the like, the functional group can be deactivated in advance by methylation or the like. When a thickener is used, the content of the thickener in the positive electrode active material layer can be, for example, 0.1% to 8% by mass, or less than 5% by mass or less than 1% by mass. The technology disclosed herein can preferably be implemented in a manner such that the positive electrode active material layer does not contain a thickener.

[0065] The filler is not particularly limited. As fillers, inorganic oxides such as polypropylene and polyethylene, silica, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, and other mineral resources or their artificial products can be cited. When a filler is used, the content of the filler in the positive electrode active material layer can be, for example, 0.1% to 8% by mass, or less than 5% by mass or less than 1% by mass. The technology disclosed herein can preferably be implemented in a manner such that the positive electrode active material layer does not contain a filler.

[0066] The positive electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, W as components other than active material particles, other positive electrode active materials, conductive agents, binders, thickeners, and fillers.

[0067] The lower limit of the density of the positive electrode active material layer is preferably 1.8 g / cm 3 , more preferably 1.9 g / cm 3 , more preferably 2.0 g / cm 3 , more preferably 2.1 g / cm 3 By making the density of the positive electrode active material layer greater than the above lower limit, the discharge capacity per unit volume of the positive electrode active material layer can be further increased. The upper limit of the density of the positive electrode active material layer can be 2.6 g / cm 3 , or 2.5g / cm 3 , 2.4g / cm 3 or 2.3g / cm 3The density of the positive electrode active material layer can be between any of the lower limits and any of the upper limits described above. The density of the positive electrode active material layer can be adjusted by the type of active material particles, the intensity of the pressing during the production of the positive electrode, and the like.

[0068] The mass per unit area of ​​the positive electrode active material layer is preferably 0.3 g / cm 2 ~3g / cm 2 , more preferably 0.5 g / cm 2 ~2.0g / cm 2 , more preferably 0.7 g / cm 2 ~1.5g / cm 2 When the mass per unit area of ​​one positive electrode active material layer is within the above range, the discharge capacity of the energy storage device can be increased.

[0069] The positive electrode can be produced, for example, by applying a positive electrode mixture paste to a positive electrode substrate, drying it, and then laminating a positive electrode active material layer along at least one surface of the positive electrode substrate. The positive electrode mixture paste, for example, contains the components constituting the positive electrode active material layer and a dispersion medium. Preferably, the positive electrode mixture paste is pressed after application and drying. Pressing can produce a high-density positive electrode active material layer.

[0070] <Electrical Storage Components>

[0071] The storage element of one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, an electrolyte, and a container for accommodating the electrode body and the electrolyte. The electrode body is generally a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are stacked via a separator. The electrolyte exists in a state contained in the positive electrode, the negative electrode and the separator. The electrolyte can be a non-aqueous electrolyte. As an example of a storage element, a non-aqueous electrolyte secondary battery (hereinafter also referred to as a "secondary battery") in which the electrolyte is a non-aqueous electrolyte is described.

[0072] (positive electrode)

[0073] The positive electrode included in the energy storage element can use the electrode described above as one embodiment of the present invention.

[0074] (negative electrode)

[0075] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The structure of the intermediate layer is not particularly limited and can be selected from the structures exemplified for the positive electrode described above.

[0076] The negative electrode substrate has electrical conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, aluminum, or alloys thereof, carbon materials, etc. can be used. Among them, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be mentioned. From the perspective of cost, foil is preferred. Therefore, copper foil or copper alloy foil is preferably used as the negative electrode substrate. Examples of copper foil include rolled copper foil, electrolytic copper foil, etc.

[0077] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within this range, the strength of the negative electrode substrate can be increased, and the energy density per unit volume of the storage device can be increased.

[0078] The negative electrode active material layer contains a negative electrode active material. Optionally, the negative electrode active material layer may contain any components such as a conductive agent, a binder, a thickener, and a filler. These components may be selected from the materials exemplified above for the positive electrode.

[0079] The negative electrode active material layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W as ingredients other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0080] As the negative electrode active material, it can be appropriately selected from known negative electrode active materials. As the negative electrode active material for lithium ion secondary batteries, materials that can absorb and release lithium ions are generally used. Examples of negative electrode active materials include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 Titanium-containing oxides such as LiTiO2, TiNb2O7, and others; polyphosphate compounds; silicon carbide; carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). Of these materials, graphite and non-graphitic carbon are preferred. The negative electrode active material layer may contain any one of these materials alone or a mixture of two or more.

[0081] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before or during charge and discharge. 002) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. From the perspective of obtaining a material with stable physical properties, artificial graphite is preferred.

[0082] “Non-graphite carbon” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge / discharge or during discharge. 002 ) is a carbon material having a diameter of 0.34 nm to 0.42 nm. Examples of non-graphite carbon include hardly graphitizable carbon and easily graphitizable carbon. Examples of non-graphite carbon include resin-derived materials, petroleum pitch or materials derived from petroleum pitch, petroleum coke or materials derived from petroleum coke, plant-derived materials, and alcohol-derived materials.

[0083] Here, the term "discharge state" refers to a state in which the carbon material serving as the negative electrode active material is discharged in such a manner that lithium ions that can be stored and released during charge and discharge are fully released. For example, this refers to a state in which the open circuit voltage of a half-cell using a negative electrode containing a carbon material as the negative electrode active material as the working electrode and metallic lithium as the counter electrode is 0.7 V or higher.

[0084] “Non-graphitizable carbon” refers to the above-mentioned 002 It is a carbon material with a diameter of 0.36nm to 0.42nm.

[0085] “Graphitizable carbon” refers to the above-mentioned 002 A carbon material having a diameter of 0.34 nm or more and less than 0.36 nm.

[0086] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be set to 1 nm to 100 μm, for example. When the negative electrode active material is a carbon material, a titanium-containing oxide or a polyphosphate compound, its average particle size can be 1 μm to 100 μm. When the negative electrode active material is Si, Sn, Si oxide or Sn oxide, etc., its average particle size can be 1 nm to 1 μm. By making the average particle size of the negative electrode active material above the above lower limit, the manufacture or handling of the negative electrode active material becomes easy. By making the average particle size of the negative electrode active material below the above upper limit, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain a powder with a specified particle size, a pulverizer, a classifier, etc. can be used. When the negative electrode active material is a metal such as metal Li, the negative electrode active material layer can be in the form of a foil.

[0087] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% to 99% by mass, more preferably 90% to 98% by mass. By setting the content of the negative electrode active material within this range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0088] (Isolator)

[0089] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator having a heat-resistant layer containing heat-resistant particles and a binder formed on one or both surfaces of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabric, non-woven fabric, porous resin film, etc. can be cited. Among these shapes, porous resin film is preferred from the viewpoint of strength, and non-woven fabric is preferred from the viewpoint of liquid retention of non-aqueous electrolyte. As the material of the substrate layer of the separator, from the viewpoint of insulation function, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of resistance to oxidative decomposition, polyimide, aromatic polyamide, etc. are preferred. As the substrate layer of the separator, a material composited with these resins can also be used.

[0090] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials that have a mass loss below the prescribed value include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalently bonded crystals such as silicon and diamond; and mineral-derived materials such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As inorganic compounds, these substances may be used singly or in complex, or in combination of two or more. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of safety of the energy storage device.

[0091] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength and preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" is a volume-based value and refers to a value measured using a mercury porosimeter.

[0092] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. Examples of polymers include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, and polyvinylidene fluoride. Using a polymer gel can effectively suppress leakage. As a separator, a porous resin film or nonwoven fabric, as described above, can also be used in combination with a polymer gel.

[0093] (non-aqueous electrolyte)

[0094] The non-aqueous electrolyte can be appropriately selected from known non-aqueous electrolytes. A non-aqueous electrolyte solution can also be used. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0095] As nonaqueous solvent, can suitably select from known nonaqueous solvent.As nonaqueous solvent, can enumerate cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, acid amides, nitrile etc.As nonaqueous solvent, also can use the solvent after the part of the hydrogen atom that comprises in these compounds is substituted by halogen.

[0096] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. Among them, EC is preferred.

[0097] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, and bis(trifluoroethyl) carbonate. Among them, EMC is preferred.

[0098] As the non-aqueous solvent, preferably a cyclic carbonate or a chain carbonate is used, more preferably a cyclic carbonate and a chain carbonate are used in combination. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted and the ionic conductivity of the non-aqueous electrolyte can be improved. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be suppressed to a low level. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is preferably in the range of 5:95 to 50:50.

[0099] As the electrolyte salt, it can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Among them, lithium salts are preferred.

[0100] Examples of lithium salts include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2; lithium oxalates such as lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiFOB), and lithium bis(oxalato)difluorophosphate (LiFOP); and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0101] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm at 20°C and 1 atmosphere. 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte solution can be improved.

[0102] In addition to the non-aqueous solvent and the electrolyte salt, the non-aqueous electrolyte may also contain additives. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiFOB), and lithium bis(oxalato)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partial hydride of terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, 3,5-difluoroanisole, and 4-fluoro-2-phenyl-1-oxo-1-yl benzoate. -Difluoroanisole and other halogenated anisole compounds; vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; vinyl sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiapentane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiapentane, thioanisole, diphenyl disulfide, dipyridine Disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tris(trimethylsilyl) borate, tris(trimethylsilyl) phosphate, tetrakis(trimethylsilyl) titanate, lithium monofluorophosphate, lithium difluorophosphate, etc. These additives may be used alone or in combination of two or more.

[0103] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass relative to the overall mass of the non-aqueous electrolyte. By making the content of the additive within the above range, the capacity retention performance or cycle performance after high-temperature storage can be improved, or safety can be further improved.

[0104] A solid electrolyte may be used as the non-aqueous electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0105] The solid electrolyte can be selected from any material that has ion conductivity and is solid at room temperature (e.g., 15° C. to 25° C.), such as lithium, sodium, and calcium. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.

[0106] In the case of lithium ion secondary batteries, examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 wait.

[0107] The shape of the electric storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, and button batteries.

[0108] Figure 1 Figure 1 shows an energy storage element 1 as an example of a prismatic battery. Note that this figure shows the interior of the container. An electrode assembly 2, comprising a positive electrode and a negative electrode wound with a separator interposed therebetween, is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0109] <Electrical Storage Device>

[0110] The energy storage element of this embodiment can be installed as an energy storage unit (battery module) composed of a plurality of energy storage elements, and can be used as a power supply for vehicles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), or as a power supply for electronic devices such as personal computers and communication terminals, or as a power supply for power storage. In this case, the technology of the present invention can be applied to at least one energy storage element included in the energy storage unit.

[0111] An energy storage device according to one embodiment of the present invention includes two or more energy storage elements and includes one or more energy storage elements according to the above-described one embodiment of the present invention (hereinafter referred to as the "second embodiment"). The technology of the above-described one embodiment of the present invention can be applied to at least one energy storage element included in the energy storage device of the second embodiment. The energy storage device may include one energy storage element according to the above-described one embodiment of the present invention and one or more energy storage elements unrelated to the above-described one embodiment of the present invention, or two or more energy storage elements according to the above-described one embodiment of the present invention may be included.

[0112] Figure 2shows an example of a power storage device 30 according to the second embodiment, which is formed by further assembling power storage units 20, each of which is composed of two or more electrically connected power storage elements 1. The power storage device 30 may include a busbar (not shown) electrically connecting the two or more power storage elements 1, a busbar (not shown) electrically connecting the two or more power storage units 20, and the like. The power storage units 20 or the power storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more power storage elements.

[0113] <Method for manufacturing an energy storage device>

[0114] The method for manufacturing the energy storage element of this embodiment can be appropriately selected from known methods. For example, the method comprises preparing an electrode assembly, preparing an electrolyte, and housing the electrode assembly and the electrolyte in a container. Preparing the electrode assembly includes preparing a positive electrode and a negative electrode, and forming the electrode assembly by stacking or winding the positive and negative electrodes with a separator interposed therebetween.

[0115] The electrolyte can be stored in the container by appropriately selecting from known methods. For example, when a non-aqueous electrolyte is used as the electrolyte, the non-aqueous electrolyte can be injected from an injection port formed in the container and then the injection port can be sealed.

[0116] <Other Implementation Methods>

[0117] It should be noted that the active material particles, electrodes, and storage elements of the present invention are not limited to the above-described embodiments, and various modifications may be made without departing from the spirit of the present invention. For example, the configuration of one embodiment may be supplemented with the configuration of another embodiment, or a portion of the configuration of one embodiment may be replaced with the configuration of another embodiment or a known technique. Furthermore, a portion of the configuration of one embodiment may be deleted. In addition, a known technique may be added to the configuration of one embodiment.

[0118] In the above embodiment, the storage element is described as a non-aqueous electrolyte secondary battery (e.g., a lithium-ion secondary battery) that can be charged and discharged. However, the type, shape, size, capacity, etc. of the storage element are arbitrary. The present invention can also be applied to various secondary batteries, capacitors such as electric double-layer capacitors and lithium-ion capacitors. The storage element of the present invention can also be a storage element other than a non-aqueous electrolyte storage element.

[0119] In the above embodiments, the positive and negative electrodes are stacked with a separator interposed therebetween. However, the electrode assembly may not include a separator. For example, a non-conductive layer may be formed on the active material layer of the positive or negative electrode, allowing the positive and negative electrodes to be in direct contact.

[0120] In the above embodiment, the electrode of the present invention is described as a positive electrode, but the electrode of the present invention may also be a negative electrode. By combining it with a positive electrode using an appropriate positive electrode active material, the electrode of the present invention can also be used as a negative electrode.

[0121] Example

[0122] The present invention is further described below with reference to the following examples. However, the present invention is not limited to the following examples.

[0123] [Example 1]

[0124] (Preparation of Active Material Particles)

[0125] Active material particles in which secondary particles of lithium iron phosphate are coated with a carbon material are obtained by the following steps.

[0126] After adding 750cm 3 2dm of ion exchange water 3 1 mol / dm 3 FeSO4 aqueous solution, and at the same time, 4 mol / dm 3 NaOH aqueous solution, 0.5 mol / dm 3 NH3 aqueous solution and 0.5mol / dm 3 An NH2NH2 aqueous solution was added to prepare an Fe(OH)2 precursor. The temperature of the reaction vessel was set to 50°C ± 2°C. Next, the prepared Fe(OH)2 precursor was removed from the reaction vessel, and 100 parts by mass of the above-mentioned Fe(OH)2 precursor was solid-phase mixed with 116 parts by mass of LiH2PO4 and 10 parts by mass of sucrose powder. Then, the obtained mixture was calcined at a calcination temperature of 650°C under a nitrogen atmosphere to obtain the active material particles of Example 1, in which particles of LiFePO4, a lithium transition metal compound having a polyanion structure, were coated with a carbon material.

[0127] The carbon material content in the active material particles of Example 1 was 1.0% by mass. The average particle size of the active material particles of Example 1, measured by the above method, was 7.5 μm. The change in particle size when the active material particles of Example 1 were subjected to a pressure increase from 20 mN to 100 mN, measured by the above method, was 0.2 nm, and the rate of change in particle size was 0.003%.

[0128] (Production of positive electrode)

[0129] A positive electrode mixture paste is prepared using the obtained active material particles, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the active material particles, AB, and PVDF is 90:5:5 in terms of solid content. The positive electrode mixture paste is applied to aluminum foil as a positive electrode substrate, dried, and roll-pressed to form a positive electrode active material layer, thereby obtaining the positive electrode of Example 1. The coating amount of the positive electrode mixture paste is 1.0 g / cm2 in terms of solid content. 2 , the roller pressure is 320kgf / cm, the roller temperature is 120℃, and the speed is 2.0m / min.

[0130] The density of the positive electrode active material layer of the positive electrode obtained in Example 1 measured by the above method was 2.2 g / cm 3 .

[0131] (Fabrication of negative electrode)

[0132] A negative electrode mixture paste was prepared by mixing graphite as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, carboxymethyl cellulose (CMC) as the thickener, and water as the dispersion medium. The mass ratio of graphite, SBR, and CMC, calculated on a solids basis, was 96:3.3:0.7. This negative electrode mixture paste was applied to copper foil, the negative electrode substrate, dried, and roll-pressed to form a negative electrode active material layer, resulting in a negative electrode.

[0133] (non-aqueous electrolyte)

[0134] In a solvent prepared by mixing ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) at a volume ratio of 30:35:35, a 1.1 mol / dm 3 LiPF6 is dissolved in a concentration of to obtain a non-aqueous electrolyte.

[0135] (Isolator)

[0136] A polyethylene microporous film was used as the separator.

[0137] (Assembly of storage elements)

[0138] The positive electrode, negative electrode, and separator were stacked to produce an electrode assembly, which was placed in a container. The nonaqueous electrolyte was then poured into the container and the container was sealed to obtain the energy storage device of Example 1.

[0139] [Examples 2 to 5, Comparative Examples 1 to 3]

[0140] In the production of active material particles, the active material particles, positive electrodes, and energy storage devices of Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the pH of the reaction solution and the concentration of the NH3 aqueous solution during the production of the Fe(OH)2 precursor were adjusted as shown in Table 1. The pH of the reaction solution was adjusted by varying the amount of each aqueous solution added. In Comparative Example 3, no NH3 aqueous solution was added.

[0141] [Comparative Example 4]

[0142] Active material particles, a positive electrode, and an electricity storage element of Comparative Example 4 were obtained in the same manner as in Example 1 except that active material particles were produced by the following solid phase method.

[0143] Li2CO3, FePO4, and sucrose powders were solid-phase mixed at a molar ratio of 1:2:1. The resulting mixture was calcined at 650°C under a nitrogen atmosphere to obtain active material particles of Comparative Example 4, comprising particles of LiFePO4, a lithium transition metal compound having a polyanion structure, coated with a carbon material.

[0144] Table 1 shows the change in particle size (particle size change) and the rate of change in particle size (particle size change rate) when the pressure was applied from 20 mN to 100 mN for each active material particle obtained by the above method, as well as the density of the positive electrode active material layer of each positive electrode.

[0145] [evaluate]

[0146] (Charge and discharge test)

[0147] For each storage element of the embodiment and comparative example, after the prescribed initial charge and discharge, a charge and discharge test was performed according to the following procedures. In an environment of 25°C, constant current and constant voltage charging was performed with a charging current of 0.1C and a charge end voltage of 3.6V. The end condition of charging was set to a total charging time of 15 hours. After a 10-minute rest period, constant current discharge was performed with a discharge current of 0.1C and a discharge end voltage of 2.0V. The discharge capacity per unit mass of the positive electrode active material layer and the discharge capacity per unit volume of the positive electrode active material layer are shown in Table 1.

[0148]

[0149] As shown in Table 1, the positive electrode active material layer density of the storage element using each of the active material particles of Examples 1 to 5, whose particle size change upon application of a predetermined pressure was 1.1 nm or less, was high, and the discharge capacity per unit volume of the positive electrode active material layer was large. Furthermore, it was found that active material particles with a particle size change upon application of a predetermined pressure of 1.1 nm or less can be obtained by using an NH3 aqueous solution and adjusting the pH to an appropriate range when producing the hydroxide precursor.

[0150] Industrial applicability

[0151] The present invention is suitable for use as a storage element, typified by a non-aqueous electrolyte secondary battery used as a power source for electronic devices such as personal computers and communication terminals, and automobiles.

[0152] Explanation of symbols

[0153] 1. Storage element

[0154] 2 Electrode body

[0155] 3 Containers

[0156] 4 Positive terminal

[0157] 41 positive lead

[0158] 5 Negative terminal

[0159] 51 Negative lead

[0160] 20 Power storage unit

[0161] 30 Power storage device

Claims

1. An active material particle, which is a granular material comprising a lithium transition metal compound having a polyanion structure and coated with a carbon material, The change in particle size when the pressure was increased from 20 mN to 100 mN was 1.1 nm or less.

2. The active material particle according to claim 1, wherein The change rate of the particle size when the pressure is increased from 20 mN to 100 mN is 0.05% or less.

3. The active material particle according to claim 1 or 2, wherein: The particles including the lithium transition metal compound having a polyanion structure are secondary particles. 4 . An electrode comprising the active material particles according to claim 1 .

5. An electrode comprising an active material layer containing the active material particles according to claim 1 or 2, The density of the active material layer is 1.8 g / cm 3 above. 6 . An electric storage element comprising the electrode according to claim 4 . 7 . A power storage device comprising two or more power storage elements and comprising one or more power storage elements according to claim 6 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2007213961A